Novel sandwich structure approach to develop lightweight concrete canoe. (2022) - Bharath, M.; Saravanan, J.; Kumar Sha, Aman; Ram Ghimire, Bal; Bhagat, Kaushal; Sherstha, Lekhnath; Ghimire, Prabin; Kasaudhan, Rahul; Sha, Sathis; Madhu, Shilpa
Graphical abstract: Abstract: Concrete canoe making is a prestigious multidisciplinary activity that relates the fields like concrete technology, hydrodynamics, material science, naval architecture, etc. Each year national and international level competitions are organized by various organizations. This work aimed to produce a lightweight single peddler concrete canoe. It was achieved by synergetic effects of the following activities: enhancing the floatability of hardened concrete; creating a maneuverable hull for a fresh paddler; enriching the structural performance of the canoe for the stress reversal for dealing with the curling effect in lightweight concrete and fabricating a canoe for a watertight environment.